Sociolinguistics in English Teaching and Ways of Developing Sociolinguistics Competences - Khakimova Dilshoda Oybek qizi; Yusupova Sevinch Shuxrat qizi (Genius Journals, 2023)
The article below presents information about sociolinguistics, its role in English teaching, and the most effective ways to enhance sociolinguistics competences. Results of worldwide researches are also provided.
Keywords: Anthropology; social classes; culture